The Spanish Banks in face of the Corporate Social Responsibility Standards: previous analysis of the financial crisis - Alcaraz, Antonio Seguí; Rodenas, Sergio Palomero (Review of Business Management, 2013)
Transparency of information in the field of CSR (Corporate Social Responsibility) is common to various standards. In recent years there has been a proliferation of standards and models for the formalization of CSR strategies. The objective is to assess the degree of implementation of standards of normalization. The analysis was conducted with data from the year 2008, coinciding with the first signs of the financial crisis, serving as a reference point to analyze the effect of the crisis. The field work was conducted using a survey answered by 57 Spanish credit institutions. We found a low degree of implementation of standards. The GRI (Global Reporting Initiative) and the ISO 14001 stood out. In view of the orientation of credit institutions towards the market, Banks have incorporated much more elaborated and comprehensive quality standards than other credit institutions, such as the implementation of the standard AS 1000 that is equivalent to the joint implementation of the ISO 14000 and 9000.